1977
DOI: 10.1007/bf00220167
|View full text |Cite
|
Sign up to set email alerts
|

The origin of the vasopressinergic and oxytocinergic fibres of the external region of the median eminence of the rat hypophysis

Abstract: The origin of the vasopressinergic and oxytocinergic nerve fibres of the external region of the rat median eminence was investigated by means of hypothalamic lesions, adrenalectomy and immunocytochemistry. The results obtained in bilaterally adrenalectomized animals with complete, or incomplete, destruction of the suprachiasmatic nuclei showed that, at least, the great majority of the vasopressinergic and oxytocinergic nerve fibres of the external region of the rat median eminence do not originate from the sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
70
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 284 publications
(73 citation statements)
references
References 15 publications
3
70
0
Order By: Relevance
“…Proenkephalinand [Met]enkephalin-immunoreactive fibers and terminals were found in the external median eminence and were concentrated in the periphery of the neurohypophysis. We found a similar distribution for oxytocin in these tissues as has been reported by others (19,25). It has been reported that another opioid peptide, dynorphin, is present in vasopressin-containing magnocellular neurons (9,13).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Proenkephalinand [Met]enkephalin-immunoreactive fibers and terminals were found in the external median eminence and were concentrated in the periphery of the neurohypophysis. We found a similar distribution for oxytocin in these tissues as has been reported by others (19,25). It has been reported that another opioid peptide, dynorphin, is present in vasopressin-containing magnocellular neurons (9,13).…”
Section: Discussionsupporting
confidence: 91%
“…The general distribution of proenkephalin IR and [Met]enkephalin IR in the hypothalamo-neurohypophyseal system was superimposable on the distribution of oxytocin. Proenkephalinand [Met]enkephalin-immunostained cell bodies were visualized in the dorsal part of the supraoptic nuclei and in the lateral peripheral part of the paraventricular nuclei, in the same areas as are found oxytocinergic cell bodies (19,25). Proenkephalinand [Met]enkephalin-immunoreactive fibers and terminals were found in the external median eminence and were concentrated in the periphery of the neurohypophysis.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Vasopressin, but not oxytocin, is synthesized in small cell bodies of neurons in the parvocellular division of the PVN that project to the external zone of the median eminence (Vandesande et al, 1977). Release of vasopressin into the hypophysial portal circulation results in the potentiation of corticotropin-releasing factor-induced adrenocorticotropin secretion from the anterior pituitary, which in turn regulates corticosterone secretion by the adrenal gland (Gillies et al, 1982).…”
Section: Introductionmentioning
confidence: 99%